Polyanionic carbohydrate doxorubicin–dextran nanocomplex as a delivery system for anticancer drugs: in vitro analysis and evaluations - Yousefpour P (Dove Medical Press, 2011)
Parisa Yousefpour1,2, Fatemeh Atyabi1, Ebrahim Vashegani Farahani3, Ramin Sakhtianchi1, Rassoul Dinarvand11Nanotechnology Research Center, Faculty of Pharmacy, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Biotechnology, Faculty of Science, University of Tehran, Tehran, Iran 3Department of Chemical Engineering, Tarbiat Modares University, Tehran, IranAbstract: This study deals with the preparation and investigation of a nanoscale delivery system for the anticancer drug doxorubicin (DOX) using its complexation with polyanionic carbohydrate dextran sulfate (DS). Dynamic light scattering, SEM, and zeta potential determination were used to characterize nanocomplexes. DOX-DS complexation was studied in the presence of ethanol as a hydrogen-bond disrupting agent, NaCl as an electrostatic shielding agent, and chitosan as a positively charged polymer. Thermodynamics of DOX-DS interaction was studied using isothermal titration calorimetry (ITC). A dialysis method was applied to investigate the release profile of DOX from DOX-DS nanocomplexes. Spherical and smooth-surfaced DOX-DS nanocomplexes (250–500 nm) with negative zeta potential were formed at a DS/DOX (w/w) ratio of 0.4–0.6, with over 90% drug encapsulation efficiency. DOX when complexed with DS showed lower fluorescence emission and 480 nm absorbance plus a 15 nm bathometric shift in its visible absorbance spectrum. Electrostatic hydrogen bonding and π-π stacking interactions are the main contributing interactions in DOX-DS complexation. Thermal analysis of DOX-DS complexation by ITC revealed that each DOX molecule binds with 3 DS glycosyl monomers. Drug release profile of nanocomplexes showed a fast DOX release followed by a slow sustained release, leading to release of 32% of entrapped DOX within 15 days. DOX-DS nanocomplexes may serve as a drug delivery system with efficient drug encapsulation and also may be taken into consideration in designing DOX controlled-release systems.Keywords: chitosan, dextran, doxorubicin, nanocomplex, anticancer, drug delivery